EKSISTENSI ADAT PERKAWINAN MELAYU DALAM KEHIDUPAN MASYARAKAT DI DESA GUNUNG SAHILAN KABUPATEN KAMPAR - Lestari, Bevi Anjelina; Tugiman, Tugiman; Ahmal, Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Customs are behaviors that are hereditary and have been in effect for a long time, with strict and binding rules. The customs and traditions in Indonesia are very diverse, one of which is the customs in Kampar about marital customs, which have certain procedures and rules determineted by local customs that are still implemented today. The purpose of this study is to find out how the intial process before marriage in the village of Mount Sahilan Kampar district, to find out how the Malay tradisional wedding procession in the village of Mount Sahilan Kampar district, to fint out how the conditions after marriage in the village Mount Sahilan Kampar district. The method is a qualitative method, where data is collected through interviews, observations, documentation and literature study. The time of the study began from the submission of the final revision of the author?s thesisi. The results showed that the Malay custom of marriage in Mount Sahilan is still maintained until now. Seen in the process before marriage which is carried out in the matchmaking is called manjodohkan, than the customary marriage procession there are nine procedures that must be carried out and the condition after the marriage procession is performed the last event called menjolangmintuo. KeyWords: Traditional, Malay, Marriage, GunungSahilan